Working memory in pre-school children with autism spectrum disorder: An eye-tracking study - Zacharov, Oleg; Huster, Rene Jürgen; Kaale, Anett (Frontiers in Psychology, 2022)
Working memory (WM) was examined in preschool children with Autism Spectrum Disorder (ASD) and children with typical development using eye-tracking technology. The children were presented with a digital A-not-B task (with a short and a long waiting condition) where they passively viewed animations of a moving train. Moreover, the current study investigated the relationship between nonverbal mental age (NMVA) and the performance on the task. No group differences were found in the average looking durations between the ASD and TD groups on either the short or longer waiting conditions. Although the NVMA of the ASD group was lower than that of the TD group there were no correlations between NVMA and task performance in either group. The results suggest that WM in young children with ASD might not be different from that of TD children. However, the results might be due to ceiling effects of the task and thus needs to be further investigated.